The concept of contract in financial technology era connected with sharia principles - Toto Tohir, Neni Sri Imaniyati, Neneng Nurhasanah, (Opción, 2019)
The purpose of this research is to describe the sharia principles as the basis of sharia banking in Indonesia. The approach was qualitative with the nature of normative juridical research. As a result, the economic relationship based on Islamic sharia consists of five concepts of contract, namely Al Wadiah (deposit), Syirkah (profit sharing), At Tijarah (selling and buying), Al Ijarah (rent), and Al-Ajr wal umummah (service or fee). In conclusion, Sharia Principles as the foundation of Islamic banking law in Indonesia refers to the general principles of Islamic law, the principles of sharia law, and general principles of Islamic Economics